Streptococcus mutans Proteases Degrade Dentinal Collagen - Bo Huang; Cameron A. Stewart; Christopher A. McCulloch; J. Paul Santerre; Dennis G. Cvitkovitch; Yoav Finer (MDPI AG, 2022)
Here, we explored the role of S. mutans's whole cell and discrete fractions in the degradation of type I collagen and dentinal collagen. Type I collagen gels and human demineralized dentin slabs (DS) were incubated in media alone or with one of the following: overnight (O/N) or newly inoculated (NEW) cultures of S. mutans UA159; intracellular proteins, supernatant or bacterial membranes of O/N cultures. Media from all groups were analyzed for protease-mediated release of the collagen-specific imino acid hydroxyproline. Images of type I collagen and DS were analyzed, respectively. Type I collagen degradation was highest for the supernatant (p < 0.05) fractions, followed by intracellular components and O/N cultures. Collagen degradation for DS samples was highest for O/N samples, followed by supernatant, and intracellular components (p < 0.05). There was lower detectable degradation for both type I collagen and DS from NEW culture samples (p < 0.05), and there was no type I collagen or DS degradation detected for bacterial membrane samples. Structural changes to type I collagen gel and dentinal collagen were observed, respectively, following incubation with S. mutans cultures (O/N and NEW), intracellular components, and supernatant. This study demonstrates that intracellular and extracellular proteolytic activities from S. mutans enable this cariogenic bacterium to degrade type I and dentinal collagen in a growth-phase dependent manner, potentially contributing to the progression of dental caries.